Elderly patients undergoing cystectomy, comparing preoperative American Society of Anesthesiology and Eastern Cooperative Oncology Group scores and operative approaches. Issue 4 (November 2019) - Martin, Christopher; West, Jeremy M; Palermo, Salvatore; Patel, Darshan P; Presson, Angela P; Comploj, Evi; Pycha, Armin; Hancock, Joel B; Dechet, Christopher B; Trenti, Emanuela
Objective: To evaluate preoperative scoring systems and operative management and their relation to complications in patients older than 75 years undergoing cystectomy at two academic institutions. Methods: In total, 212 patients aged 75–95 years with muscle invasive bladder cancer underwent cystectomy at the University of Utah and Central Hospital of Bolzano, Italy. The rates of Grade 3 Clavien-Dindo complications and above in radical cystectomy patients (n = 199) were compared using Eastern Cooperative Oncology Group Scores and American Society of Anesthesiologists Physical Status Classification. The rates of Grade 3 Clavien-Dindo complications and above were also compared by urinary diversion type. Logistic regression was used to control for source institution. Results: In total, 199 cases were included in the primary analysis. Neither of the preoperative scoring systems were predictive for identification of radical cystectomy patients with ⩾Grade 3 Clavien-Dindo complications. In secondary analysis (n = 212, including partial cystectomy), none of the urinary diversion types associated with radical cystectomy had a significantly different rate of complications. However, partial cystectomy (n = 13) had a significantly lower rate of complications. Conclusion: Complication rates among elderly patients undergoing cystectomy for muscle invasive bladder cancer were very high. For patients who are approved for surgery after the history and physical exam, none of our objective metrics adequately predicted operative risk. A unique diversion procedure described by the Bolzano group, uretero-ureterocutaneostomy, had equivalent complication rates to the more common diversion procedures. It also appears based on outcomes in this cohort that partial cystectomy is a particularly favorable option within the elderly population in terms of perioperative morbidity.